GESTATIONAL DIABETES MELLITUS: A MODERN VIEW ON THE ACTUAL PROBLEM - M.F. DODKHOEVA; D.A. PIRMATOVA (Паёми Сино, 2018)
A review of world literature has shown that gestational diabetes mellitus (GDM) is the most frequently encountered extra genital pathology of gestation and represents a serious medical and social problem, increasing the incidence of unwanted pregnancy outcomes for both the mother and the fetus. Significant variability of opinions on the frequency of GDM, its etiology and pathogenesis, screening methods and diagnostics of impaired carbon-water metabolism revealed during the pregnancy. Considering the diverse scientific data, constantly changing bio ecological environmental conditions that drastically affect the development of pregnancy, it is necessary to note the need for early detection of GDM in order, to adequately correct glycaemia to prevent an adverse course of pregnancy and childbirth. The lack of universal diagnostic criteria, on the one hand, and the clinical course of GDM without obvious manifestations, on the other hand, subsequently increase the risk of diabetes, obesity, carbohydrate metabolism disorders and cardiovascular complications in both mother and child. Consequently, this pathology requires the development of uniform standards for the diagnosis and treatment of disorders of carbohydrate metabolism during the pregnancy.